Strategi Penggunaan Cargo Pump sebagai Upaya dalam Menunjang Kelancaran Bongkar Crude Palm Oil di Kapal MT Koan - Jeffy Maulidi Feriyanto; Ari Sriantini; Dedy Kristiawan (Populer: Jurnal Penelitian Mahasiswa, 2024)
Cargo pumps are very important in the unloading process, especially crude palm oil cargo on tankers. In order for the cargo unloading process to run smoothly, a strategy is needed in the use of cargo pumps. This study aims to find out the factors that cause damage to cargo pumps and the strategy of using cargo pumps so that the process of dismantling crude palm oil in MT Koan can run smoothly. The research method used is qualitative descriptive with data collection techniques through observation and interviews. The results showed that cargo pump 1 operated better than cargo pump 2, with 77% of the operating time. Damage to the cargo pump is caused by leaks in the mechanical seal and clogging of dirt. Routine maintenance on cargo pump 1 is more frequent than cargo pump 2. The cargo temperature of crude palm oil is relatively low ranging from 39-40°C and there is a decrease in temperature at one observation point which causes the texture of the cargo to become very thick, thus interfering with the performance of the cargo pump. Based on the results of data analysis of the results of observations and interviews, it can be concluded that the factors that cause damage to cargo pumps at MT Koan are lack of maintenance, low load temperature and performance differences in both cargo pumps.